Leading Effectively in a VUCA Environment: A is for Ambiguity - Kail, Col Eric G. (Harvard Business Review, 2011)
This is the last in a series on the four aspects of VUCA, a framework used by the U.S. military to describe the environment in terms of vola tility, uncertainty, complexity, and ambiguity. Diversity and global r each introduce ambiguity to the environment; therefore opportunities a nd challenges must be appreciated from multiple aspects, not just our own […]
Keywords: Leadership; Leading teams